Hambatan Guru dalam Melaksanakan Prosedur Pengembangan Evaluasi Pembelajaran Bahasa Indonesia Pada Masa Pandemi di SMA Negeri 5 Pekanbaru - Sri Murni; Muhammad Mukhlis (UIR Press, 2022)
This research was motivated by the obstacles found in carrying out evaluation procedures during the pandemic at SMA Negeri 5 Peknabaru. The purpose of the study was to determine the teacher's obstacles in carrying out the procedures for developing an evaluation of Indonesian learning during the pandemic at SMA Negeri 5 Pekabaru. The theory used is the theory of Zainal Arifin with the title